2022
DOI: 10.1111/desc.13267
|View full text |Cite
|
Sign up to set email alerts
|

Threat and deprivation are associated with distinct aspects of cognition, emotional processing, and psychopathology in children and adolescents

Abstract: Exposure to childhood adversity has been consistently associated with poor developmental outcomes, but it is unclear whether these associations vary across different forms of adversity. We examined cross‐sectional and longitudinal associations between threat and deprivation with cognition, emotional processing, and psychopathology in a middle‐income country. The sample consisted of 2511 children and adolescents (6–17 years old) from the Brazilian High‐Risk Cohort for Mental Conditions. Parent reports on childh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 71 publications
2
23
0
Order By: Relevance
“…TIC can be seen as a “system development model that moves away from the traditional diagnosis model of “what is wrong with you”, towards a story-based approach of “what happened to you” [ 47 ]. TIC has four key elements, referred to as the four Rs: Realizing the widespread impact of trauma, Recognizing how trauma may affect individual clients, staff or others in the program, Responding by applying knowledge about trauma into practice and Resisting retraumatization [ 48 ].…”
Section: Adverse Childhood Experiences Protective and Compensatory Ex...mentioning
confidence: 99%
“…TIC can be seen as a “system development model that moves away from the traditional diagnosis model of “what is wrong with you”, towards a story-based approach of “what happened to you” [ 47 ]. TIC has four key elements, referred to as the four Rs: Realizing the widespread impact of trauma, Recognizing how trauma may affect individual clients, staff or others in the program, Responding by applying knowledge about trauma into practice and Resisting retraumatization [ 48 ].…”
Section: Adverse Childhood Experiences Protective and Compensatory Ex...mentioning
confidence: 99%
“…When considering childhood PA factors, particularly maltreatment, most studies have reported greater exposure to PA associated with poorer inhibitory control behavioral outcomes, however some studies reported a lack of significant findings (Carvalho et al, 2020; Lund et al, 2020; Augusti & Melinder, 2013). In light of varying results, rather than considering the cumulative effects of PA as previously done, greater attention is aimed at characterizing and identifying the impacts of the specific forms of adversity as they can manifest in different ways in a developing brain (Felitti et al, 1998; Schäfer et al, 2023). When various types of adversity are assessed as a single factor, developmental differences that may relate to these types of PA are unable to be distinguished whereas these factors may affect brain development differently if they were considered individually (McLaughlin, 2016; Schäfer et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In light of varying results, rather than considering the cumulative effects of PA as previously done, greater attention is aimed at characterizing and identifying the impacts of the specific forms of adversity as they can manifest in different ways in a developing brain (Felitti et al, 1998; Schäfer et al, 2023). When various types of adversity are assessed as a single factor, developmental differences that may relate to these types of PA are unable to be distinguished whereas these factors may affect brain development differently if they were considered individually (McLaughlin, 2016; Schäfer et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Experiences classified under the threat dimension correspond to the act of commission that typically includes physical/corporal punishment, harsh discipline, sexual abuse, and psychological aggression (Duprey et al, 2022; Liu et al, 2020). Deprivation‐related experiences constitute acts of omission, such as neglectful behaviors (e.g., physical, emotional, medical, and educational neglect; Liu et al, 2020; Schäfer et al, 2022; Weber et al, 2016). Studies suggest that experiences of child maltreatment disrupt downstream development, placing adolescents at risk for mental health problems, such as heightened levels of negative affect (Azarmehr et al, 2020; Lippard & Nemeroff, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence shows that the child maltreatment dimensions are differentially linked with youth's psychopathology and adjustment. Adolescents exposed to threat in their childhood (e.g., physical and emotional abuse) have problems with social‐emotional processing (Schäfer et al, 2022), resulting in disrupted emotion regulation (Miller et al, 2018; Shackman & Pollak, 2014), whereas deprived adolescents (e.g., emotionally and physically neglected) are more likely to experience deficits in the development of cognitive function (e.g., problem solving; Berman et al, 2022; Chahal et al, 2022; Schimmenti et al, 2015). Moreover, childhood threat and deprivation experiences may have a negative and long‐lasting impact on emotional states and increase the risk of experiencing increased negative affect (Turiano et al, 2017; Xiang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%